2016
DOI: 10.1111/age.12511
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and phylogeographic structure of Bactrian camels shown by mitochondrial sequence variations

Abstract: SummaryThe Bactrian camel includes various domestic (Camelus bactrianus) and wild (Camelus ferus) breeds that are important for transportation and for their nutritional value. However, there is a lack of extensive information on their genetic diversity and phylogeographic structure. Here, we studied these parameters by examining an 809‐bp mtDNA fragment from 113 individuals, representing 11 domestic breeds, one wild breed and two hybrid individuals. We found 15 different haplotypes, and the phylogenetic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 15 publications
2
28
3
Order By: Relevance
“…These parameters were 0.453 and 0.00109 for the Joudibreed and 0.648 and 0.00175 for the Hurrabreed while the values were zero for the Khwarbreed (Table 1). Our results were less than the results of Ming et al (2016b) in his study 11 breeds of domestic camelin China, Mongolia, Russia and a group of two-hump wild camels of Mongolia which ranged from 0.456 and 0.0011 to 0.900 and 0.0032 respectively. As well as Abdussamad et al (2015) found higher variability (0.751 and 0.002 respectively) in Nigerian camel, found 0.833 and 0.00187, respectively, in Pakistani camels.…”
Section: Sequence Variation and Genetic Diversitycontrasting
confidence: 87%
See 2 more Smart Citations
“…These parameters were 0.453 and 0.00109 for the Joudibreed and 0.648 and 0.00175 for the Hurrabreed while the values were zero for the Khwarbreed (Table 1). Our results were less than the results of Ming et al (2016b) in his study 11 breeds of domestic camelin China, Mongolia, Russia and a group of two-hump wild camels of Mongolia which ranged from 0.456 and 0.0011 to 0.900 and 0.0032 respectively. As well as Abdussamad et al (2015) found higher variability (0.751 and 0.002 respectively) in Nigerian camel, found 0.833 and 0.00187, respectively, in Pakistani camels.…”
Section: Sequence Variation and Genetic Diversitycontrasting
confidence: 87%
“…These results suggest that Iraqi camel breeds evolve differently than other studied breeds in other countries. Similar results were demonstrated by Ming et al (2016b), who found two haplogroups for domestic and wild Bactrian camel. In comparison with some countries, the results showed that Cytb has two main branches: the first branch includes the Iraqi camels and the second branch branche divided into two branches.…”
Section: Sequence Variation and Genetic Diversitysupporting
confidence: 87%
See 1 more Smart Citation
“…camel was relatively close, which may be related to its geographical distribution. It indicated that most of the mitochondrial haplotypes of domestic Bactrian camels were shared, supporting the claim that the domestic Bactrian camels belonged to the single maternal origin(Ming et al, 2017). RAD-seq technology includes DNA sequence data from multiple loci in the genome at a lower cost, simpler library preparation process, no prior knowledge of any locus DNA sequences, management of data from simplified genomes, and well-developed pipelines for data treatment and analysis to retrieve orthologous sites for comparison(Eaton & Ree, 2013;McCormack, Hird, Zellmer, Carstens, & Brumfield, 2013;Rubin, Ree, & Moreau, 2012;Zhou et al, 2018).…”
mentioning
confidence: 60%
“…This indicated that many genes were moved to new chromosomal regions in the last 50 million years. Ming et al (2016) In plants, the gene flow takes place through pollens and seeds, which means that the geographic system of genetic changes was generated by two different mechanisms (Hamilton & Miller, 2002;Levin, 1981;Sork, Smouse, Grivet, & Scofield, 2015). The important feature of plant dispersal is that we can notice whether genes are distributed through dispersal of seed or pollen.…”
Section: Gene Movementsmentioning
confidence: 99%